Hubungan Pengetahuan Ibu Tentang Gizi Dan Pendapatan Orang Tua Terhadap Peilaku Konsumsi Buah Dan Sayur Pada Balita 6 Bulan - 5 Tahun Di Wilayah Kerja Puskesmas Peusangan Selatan Kabupaten Bireuen - Nafis, Maghfiratun; Safitri, Dessy Widya; Pelupessy, Grace Yosephine; Tanjung, Putri Habibah; Marbun, Rasyida Afifah; Wilda, Zahratul; Haryana, Nila Reswari (Jurnal Ilmiah Wahana Pendidikan, 2025)
Indonesia is a country with a low level of fruit and vegetable consumption. Based on Riskesdas 2018, 95.5% of toddlers do not consume fruits and vegetables. Based on WHO, the level of fruit and vegetable consumption of toddlers is still relatively low, namely 95%. Lack of fruit and vegetable intake will result in a risk of death from digestive tract cancer of 14%, a risk of death from coronary heart disease of 11%, and death from stroke of 9%. Based on this background, researchers are interested in conducting research on "The Relationship between Mother's Knowledge About Nutrition and Parental Income to Fruit and Vegetable Consumption Behavior in Toddlers Aged 6 months - 5 years in the Peusangan Selatan Health Center Work Area, Bireuen Regency". The purpose of this study was to determine the knowledge of mothers about nutrition who have toddlers aged 6 months - 5 years in the Peusangan Seulatan Health Center work area, Bireuen Regency. Not only that, this study aims to determine how the income of parents, and the behavior of fruit and vegetable consumption in toddlers aged 6 months - 5 years in the work area of ​​the Peusangan Seulatan Health Center, Bireuen Regency. This type of research is quantitative research with a cross-sectional method. Data collection techniques were carried out by interviews using questionnaires. The descriptive data analysis technique used the chi-square test. Based on the results of the chi-square test, it is known that there is a significant relationship between maternal knowledge about nutrition and fruit and vegetable consumption behavior in toddlers aged 6 months - 5 years in the work area of ​​the Peusangan Seulatan Health Center, Bireuen Regency with p = 0.00 <0.05). While for the variable of parental income, there is no significant relationship between parental income and fruit and vegetable consumption behavior in toddlers aged 6 months-5 years in the work area of ​​the Peusangan Seulatan Health Center, Bireuen Regency with p = 0.058 > (0.05).